2000
DOI: 10.3758/bf03209348
|View full text |Cite
|
Sign up to set email alerts
|

The rereading effect: Metacomprehension accuracy improves across reading trials

Abstract: Guided by a hypothesis that integrates principles of monitoring from a cue-based framework of metacognitivejudgments with assumptions about levels of text representation derived from theories of comprehension, we discovered that rereading improves metacomprehension accuracy. In Experiments 1 and 2, the participants read texts either once or twice, rated their comprehension for each text, and then were tested on the material. In both experiments, correlations between comprehension ratings and test scores were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 29 publications
8
122
0
7
Order By: Relevance
“…Moreover, the accuracy of the delayed-keyword group was as high as any other reported in the literature (only Rawson et al, 2000, andWeaver &Bryant, 1995, showed monitoring accuracy near the level of the delayed-keyword group).…”
Section: Monitoring Accuracysupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, the accuracy of the delayed-keyword group was as high as any other reported in the literature (only Rawson et al, 2000, andWeaver &Bryant, 1995, showed monitoring accuracy near the level of the delayed-keyword group).…”
Section: Monitoring Accuracysupporting
confidence: 60%
“…This is not an insignificant methodological difference, given that baseline levels of monitoring accuracy for texts are quite low (Glenberg, Sanocki, Epstein, & Morris, 1987;Maki, 1998) and that most attempts to improve comprehension monitoring have produced less than impressive results (cf. Rawson, Dunlosky, & Thiede, 2000, who achieved relatively high levels of monitoring accuracy by instructing participants to reread texts prior to rating comprehension). For example, Maki and Serra (1992) showed that practice tests had only a modest effect on monitoring accuracy-and only when the practice tests were identical to the eventual tests of comprehension.…”
Section: Factors Influencing the Accuracy Of Metacognitive Monitoringmentioning
confidence: 99%
“…One reason to suspect that children may struggle to monitor their own learning in a more complex task, like reading, is that learning these materials may demand more cognitive resources than more simple tasks, which may leave fewer resources for monitoring learning (Rawson, Dunlosky, & Thiede, 2000). This could be particularly important with children, as Roebers, von der Linden, and Howie (2007) showed that cognitive resources play an important role in children's monitoring.…”
Section: Monitoring Accuracymentioning
confidence: 99%
“…As Weaver (1990) and others have noted (Rawson, Dunlosky & Thiede, 2000;Weaver, Bryant, & Burns, 1995) In terms of these levels, it is the creation of the situation model that can be seen as the process of deeply understanding a text, or comprehension, and acquiring the information so that it can be used in novel contexts (Kintsch, 1994). While the surface and text-base levels can be seen as memory-based representations of the exact words and ideas that appeared in a text, the situation model represents the instantiation of both explicit and implicit relations between ideas.…”
Section: What Do We Mean By "Comprehension"?mentioning
confidence: 99%
“…This section presents an analysis of several of the one paragraph passages that have been used in so many studies on metacomprehension, originally introduced by Glenberg and Epstein (1985). The original and revised texts have been used in a large portion of the studies in this literature (Glenberg, Sanocki, Epstein, & Morris, 1987;Lin, Moore & Zabrucky, 2001; Lin, Zabrucky & Moore, 1997; Maki & Serra, 1992a, b;Magliano, Little & Graesser, 1993;Morris, 1990;Rawson, Dunlosky & McDonald, 2002;Rawson, Dunlosky & Thiede, 2000;Weaver, 1990). While to an outsider it is striking that such a large portion of a literature has utilized the same set of texts, it is understandable when investigators were concerned with aligning the effects of new manipulations with previous results.…”
mentioning
confidence: 99%